Total power - Mills, Kyle, 1966-; Flynn, Vince, 1966-2013 (Flynn, Vince, 1966-2013. Mitch Rapp novel., 2020)
When an ISIS plot devastates America's power grid, Mitch Rapp and his CIA team race to find the responsible cyberterrorists to prevent the nation from succumbing to total collapse.